Taxonomic notes on owlflies from Pakistan (Neuroptera: Myrmeleontidae: Ascalaphinae) - Hassan, Muhammad Asghar; Liu, Xingyue (Zootaxa, 2021)
Taxonomic notes are presented on the former Ascalaphidae (owlflies), now subfamily Ascalaphinae of the family Myrmeleontidae from Pakistan. An updated checklist of new records is provided that accounts for all known 15 genera and 22 species from Pakistan, excluding the species of the tribe Palparini. Geographical distribution maps and an updated identification key to all known genera and species from Pakistan are also given. We synonymized two monotypic genera, Horischema Mészáros & Ábrahám, 2003 and Perissoschema Mészáros & Ábrahám, 2003 both as junior synonyms of Ogcogaster Westwood, 1847 based on very similar male genitalia and external morphological characters. Moreover, Perissoschema evae Mészáros & Ábrahám, 2003 is treated as a junior synonym of Ogcogaster segmentator Westwood, 1847. We recorded three genera for the first time from Pakistan, i.e., Acheron Lefèbvre, 1842, Glyptobasis McLachlan, 1873, and Suphalomitus van der Weele, 1909. To more completely resolve the generic or specific status of those poorly known species from Pakistan, broader sampling throughout the country is needed.